2013
DOI: 10.1212/wnl.0b013e3182a6cbfe
|View full text |Cite
|
Sign up to set email alerts
|

Antisaccade task reflects cortical involvement in mild cognitive impairment

Abstract: The AS task is a useful measure of executive function across the AD spectrum. In MCI, AS performance may reflect disease burden within cortical brain regions involved in oculomotor control; however, AS impairments in NE may have etiologies other than incipient AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
81
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(94 citation statements)
references
References 31 publications
12
81
1
Order By: Relevance
“…37 Aging is associated with deterioration of saccadic eye movemnt 38 that may be due to age-related changes of the frontal cortex that mediate saccade generation, 38 and such effects may become even more pronounced in AD due to structural alterations of the frontal lobe. Abnormal saccadic eye movement may be an early indicator of AD, 19 and an anti-saccade task has been linked with structural alterations in frontoparietal brain regions in patients with AD, but not in normal elderly. 19 As such, poorer performance on the K-D may be capturing distinct AD-related pathological changes that affect saccadic oculomotor function, but this possibility awaits empirical test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…37 Aging is associated with deterioration of saccadic eye movemnt 38 that may be due to age-related changes of the frontal cortex that mediate saccade generation, 38 and such effects may become even more pronounced in AD due to structural alterations of the frontal lobe. Abnormal saccadic eye movement may be an early indicator of AD, 19 and an anti-saccade task has been linked with structural alterations in frontoparietal brain regions in patients with AD, but not in normal elderly. 19 As such, poorer performance on the K-D may be capturing distinct AD-related pathological changes that affect saccadic oculomotor function, but this possibility awaits empirical test.…”
Section: Discussionmentioning
confidence: 99%
“…16 Saccadic eye movement impairments are one of the most commonly documented forms of oculomotor dysfunction in AD patients, 1719 and have been recently reported in patients with the posterior cortical atrophy variant of AD. 20 Additional studies have also demonstrated that patients with amnestic MCI exhibit abnormal saccades.…”
Section: Introductionmentioning
confidence: 99%
“…Other cognitive measurements have also been used in MCI and AD. For example, an anti-saccade task is a measurement for executive function and correlated with AD-sensitive cortical thickness in MCI subjects, but not in normal elderly patients as reported by Heuer [108]. A study using a new cognitive test, hard test your memory (H-TYM), in 97 mild AD/MCI and 200 control subjects demonstrated a significant detection of mild AD/MCI who “pass” the MMSE from controls [109].…”
Section: Sex Differences In Cognitionmentioning
confidence: 99%
“…14,17,18,20 Antisaccades may provide not only a functional index of the dorsolateral prefrontal cortex, which is damaged in the later stages of AD, but also a tool for monitoring the progression of AD. 6 A more recent study 21 used an antisaccadic paradigm as a way of testing inhibitory control in AD patients. The results showed that AD patients were impaired relative to the mild cognitive impairement in participants and healthy controls.…”
Section: Clinical Ocular Motor Manifestationsmentioning
confidence: 99%